2020
DOI: 10.1038/s41598-020-73292-w
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri DSM 17938 and ATCC PTA 5289 ameliorates chemotherapy-induced oral mucositis

Abstract: Oral mucositis (OM) is a common complication of cancer therapy, however OM management remains unsatisfactory. There is a growing interest in the therapeutic potential of probiotics in OM due to positive findings of its use in intestinal mucositis. This study aimed to determine the efficacy and safety of the probiotic combination Lactobacillus reuteri DSM 17938 and ATCC PTA 5289 strains in chemotherapy-induced OM. Mice were divided into 4 groups. PBS/water and PBS/LR groups comprised of mice injected with PBS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
(47 reference statements)
1
9
0
Order By: Relevance
“…A standard S. aureus (ATCC-25923) , E coli (ATCC-25922) , P. aeroginosa (ATC-27853C), and C. albicans (ATCC-10231) preserved and archived in 15% glycerol, were revived by culturing it in nutrient and Saborauds dextrose agar [ 30 ], [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…A standard S. aureus (ATCC-25923) , E coli (ATCC-25922) , P. aeroginosa (ATC-27853C), and C. albicans (ATCC-10231) preserved and archived in 15% glycerol, were revived by culturing it in nutrient and Saborauds dextrose agar [ 30 ], [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…After stimulation, Nrf2 separates from Keap1, translocates into the nucleus, and then combines with the antioxidant response elements (AREs) and upregulates the expression of key genes including HO-1 and NQO1 [ 44 ]. Oral mucosal cell knockout of Nrf2 failed to induce the synthesis of antioxidant genes [ 45 ]. Braun et al found that the expression of various key players involved in wound healing was significantly reduced in Nrf2 knockout animals [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have attempted to explain the mechanisms underlying the development of oral mucositis. In mice, lactobacillus reuteri exerted a protective effect on 5-fluorouracil-induced oral mucosal damage [ 37 ]; lactobacillus reuteri not only downregulated NF-κB activation and pro-inflammatory cytokine expression, but also mediated the antioxidative effect through nuclear factor erythroid 2-related factor 2, a key transcription factor in mitigating oxidative stress [ 38 ]. Another animal study reported that Streptococcus salivarius K12 exerted a preventive effect on radiotherapy-induced oral mucositis in mice by modulating oral microbiota and improving microbial dysbiosis, which is involved in the development and progression of oral mucositis following radiotherapy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%